Bioanalytical method validation for therapeutic drug monitoring of olaparib in patients with ovarian cancer - Konrad Lewandowski; Agnieszka Karbownik; Andrzej Czyrski; Hanna Urjasz; Joanna Stanisławiak-Rudowicz; Edmund Grześkowiak; Edyta Szałek (Polskie Towarzystwo Farmaceutyczne, 2024)
Olaparib, an oral poly-ADP ribose polymerase (PARP) inhibitor, is a relatively new anticancer drug. It is essential to find TDM-guided dosage for better safety and tolerability of patients. However, first, it is important to develop a suitable analytical method to conduct reliable TDM. The aim of the study was the validation of UPLC-MS/MS method for TDM of olaparib in patients with ovarian cancer, with a particular attention to optimization of recovery. The validation of the method under analysis were accomplished by the ICH guidelines. The recovery of olaparib was optimized with the Central Composite Design (CCD). The TDM study was conducted on 10 patients with ovarian cancer treated with olaparib. The method validation was characterized by good precision (CV <9.09%), accuracy (89.23-111.08%) and linearity (r=0.9993) within the range of 100-20,000 ng/mL, with limits of detection of 30 ng/mL. The ten-minute shaking time combined with 100% acetonitrile resulted in an estimated value of 98% for recovery and the observed value of 98%. The olaparib concentrations in the patients' plasma were 1078.2-16773.8 ng/mL. A wide range of olaparib concentrations was observed in the patients reported adverse reactions included: anemia (grade 1, n=2), neutropenia (grade 1, n=1), and hyperkeratinemia (grade 1, n=1). The method validation included all required procedures showing that the measurement of olaparib concentrations in the plasma was reliable for the intended application, such as TDM.